RESOR DAN SPA KESEHATAN DENGAN PENDEKATAN KONSEP HEALING ENVIRONMENT DI KAWASAN PEMANDIAN AIR HANGAT CUMPLENG, TAWANGMANGU - Warih Suryo Perbowo; Edi Pramono Singgih; Mohammad Asrori (ARSITEKTURA, 2016)
The design of Health Resort and Spa is considered by urban people health concerns due to the high level of anxiety as well as unhealthy life pattern. Urban people tend to issuing high cost to restore their physical and psychological conditions. This tendency can be captured as one of the potential to develop a health resort and spa. The purpose of this design is to get a building design that can embody the activity of a health resort and spa that is integrated with the Cumpleng Warm Spring in a Healing Environment or design environment that provides therapeutic effect for visitors. The question of the design to be resolved include: designing the facilities at the resort and spa that are able to maximize the potential of Cumpleng Warm Spring; site designing that support the activities therein; landscape designing that suit to the needs of the users of the building; applying the healing environment concept in shape, appearance, and interior of the building. The used method is a method of designing architecture with the approach of the concept of a healing environment. The result is a resort and spa with health and fitness facilities that is integrated with the Cumpleng Warm Spring area that serve an environment with therapeutic effects to restore physical and psychological condition of the visitors.